TDP-43 protein in plasma may index TDP-43 brain pathology in Alzheimer’s disease and frontotemporal lobar degeneration - Foulds, Penelope; McAuley, Erica; Gibbons, Linda; Davidson, Yvonne; Pickering-Brown, Stuart M.; Neary, David; Snowden, Julie S.; Allsop, David; Mann, David M. A. (Acta neuropathologica, 2008)
Autopsy studies have shown that about 55% of patients with frontotemporal lobar degeneration (FTLD) and 25% of patients with Alzheimer’s disease (AD) harbour TDP-43 immunoreactive pathological changes in their brains. Using ELISA, we investigated whether we could detect the presence, or increased amounts, of TDP-43 in plasma of patients with FTLD and AD compared to normal control subjects. We detected elevated levels of TDP-43 protein in plasma of 46% patients with FTLD with clinical frontotemporal dementia (FTD) and 22% patients with AD, compared to 8% of control subjects. The proportions of patients with FTD and AD showing raised plasma TDP-43 levels correspond closely to those proportions known from autopsy studies to contain TDP-43 pathological changes in their brains. Raised TDP-43 plasma levels may thereby index TDP-43 pathology within the brain. Plasma TDP-43 levels may be a biomarker that can provide a laboratory test capable of identifying the presence of TDP-43 brain pathology in neurodegenerative disease during life. It may help to distinguish those cases of FTLD with ubiquitin/TDP-43 pathology in their brains from those with tauopathy. As a predictive test, plasma TDP-43 level may have great practical value in directing therapeutic strategies aimed at preventing or removing tau or TDP-43 pathological changes from the brain in FTLD and AD.